2021
DOI: 10.1177/1120672121995343
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of visual outcomes after bilateral implantation of an advanced or conventional monofocal intraocular lens

Abstract: Purpose: To assess the clinical outcomes and patient satisfaction of the Tecnis Eyhance, an advanced monofocal intraocular lens (IOL), compared to a conventional monofocal IOL. Design: Retrospective case-control study. Methods: This study included 120 eyes of 60 patients (30 patients in each group) who underwent bilateral cataract surgery either with the implantation of conventional monofocal IOLs (Tecnis PCB00), as a control group, or advanced monofocal IOLs (Tecnis Eyhance ICB00). Ophthalmological evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
32
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 8 publications
(9 reference statements)
8
32
4
1
Order By: Relevance
“…In agreement with previous studies [24][25][26][27] , the present study found excellent distance and intermediate visual outcomes in both the Emmetropia and Mini-monovision groups, as all participants underwent bilateral implantation of the Eyhance IOL. There were no statistically significant differences in the refractive error or the binocular UDVA and UIVA between groups, and the absolute visual outcome values in eyes that were bilaterally targeted for emmetropia were similar to those of available results [24][25][26][27] . However, the binocular UNVA was significantly better in the Mini-monovision group than in the Emmetropia group.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies [24][25][26][27] , the present study found excellent distance and intermediate visual outcomes in both the Emmetropia and Mini-monovision groups, as all participants underwent bilateral implantation of the Eyhance IOL. There were no statistically significant differences in the refractive error or the binocular UDVA and UIVA between groups, and the absolute visual outcome values in eyes that were bilaterally targeted for emmetropia were similar to those of available results [24][25][26][27] . However, the binocular UNVA was significantly better in the Mini-monovision group than in the Emmetropia group.…”
Section: Discussionsupporting
confidence: 93%
“…Although no control lens was used on this study, the mean binocular DCIVA of the ISOPure IOL was 0.2 logMAR, which is between 0.1 and 0.05 logMAR lower than the DCIVA reported for the ICB00 in different studies [ 18 – 20 ] and in good agreement with pre-clinical simulations. In contrast, the distance VA was slightly better for the ISOPure (-0.09 ± 0.06 logMAR) compared to the results reported for the ICB00 (ranging between − 0.06 ± 0.01 logMAR [ 19 ] and 0.03 ± 0.09 logMAR [ 23 ]).…”
Section: Discussionmentioning
confidence: 60%
“… 8 , 25 , 33 , 37 , 45 47 However, it showed poor optical quality compared to the ICB00, which showed results similar to those for monofocal IOLs. 3 , 14 , 21 , 34 …”
Section: Discussionmentioning
confidence: 99%